In the clutches of melancholy. Interpretive analysis of Gilles Renard’s student film “Late Afternoon” - Drąg, Franciszek (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2019)
The aim of the analysis is to present the film (Late Afternoon) by Gilles Renard as a study of melancholy. Both the plot and the cinematographic means used to shape the form of this short film correspond with the theoretical texts by Julia Kristeva and Melanie Klein on depression in women. The author of the text considers Late Afternoon as a feminist and affirmative film, strongly inspired by the aesthetics of Krzysztof Kieślowski’s cinematic output.